2002
DOI: 10.1046/j.1365-2141.2002.03445.x
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cells from patients with homozygous sickle cell disease provide a catalytic surface for factor Va inactivation by activated protein C

Abstract: The structure of red blood cell (RBC) membranes in homozygous sickle cell disease (SCD) is significantly disturbed, with an increased exposure of aminophospholipids (phosphatidylserine and phosphatidylethanolamine) at the outer surface, responsible for a procoagulant activity of SS RBCs. Aminophospholipids are known not only to promote procoagulant reactions, but also to support inhibition of blood coagulation by the protein C system. The aim of the present study was to examine whether SS RBCs could serve as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…We found a relation of total protein S to hemoglobin levels in our HbSS patients. Both protein S and protein C can exert their anticoagulant effects on phosphatidylserine expressing sickle red blood cell membranes [7,8,10]. In patients with lower hemoglobin levels, there are more dense cells and membrane-shed vesicles, as well as reticulocytes (which all have high phosphatidylserine exposure) [44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found a relation of total protein S to hemoglobin levels in our HbSS patients. Both protein S and protein C can exert their anticoagulant effects on phosphatidylserine expressing sickle red blood cell membranes [7,8,10]. In patients with lower hemoglobin levels, there are more dense cells and membrane-shed vesicles, as well as reticulocytes (which all have high phosphatidylserine exposure) [44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Large-vessel thrombosis causes and/or contributes to SCD-related cerebral and pulmonary complications, and some studies have suggested that reduced levels of protein S and C are associated with an increased stroke risk in patients with SCD [15][16][17][18]. Membrane-bound activated protein C, in conjunction with cofactor protein S, inactivates activated factors V and VIII, thereby blocking thrombin generation [8]. The etiology of reduced levels of NOAC in SCD is not firmly established but may involve increased consumption, decreased synthesis, or both [15,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are few studies of the anticoagulant APC-system in relation to eryMPs. It has been shown that irreversibly sickled red blood cells and eryMPs can bind protein S [18] and that the red blood cells from sickle cell disease patients support APC-mediated degradation FVa [19]. In addition, platelet-derived MPs were recently shown to stimulate APC-mediated regulation of coagulation in a protein S dependent manner through degradation of both FVa and FVIIIa [20].…”
Section: Introductionmentioning
confidence: 99%
“…14,15,28,45 Foremost among the many cerebrovascular manifestations is ischemic disease, the complex pathophysiology of which is thought to result from a combination of small and large vessel changes, coupled with abnormal red cell rheology and a hypercoagulable state. 2,4,5,18,29,47 Cerebral aneurysms, which tend to occur in multiples and have a predilection for the posterior circulation, have also been widely described in association with SCD. 3,7,8,10,23,34,35 Based on a review of the literature, however, the description of a cerebral AVM in a patient with SCD has not yet been reported.…”
mentioning
confidence: 98%